Dampak Risiko Pajak, Kualitas Audit, Kepemilikan Institusi, Kepemilikan Manajerial dan Ukuran Perusahaan terhadap Biaya Modal pada Perusahaan Manufaktur Sektor Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Stenny Anggela; Moch Irsad (Universitas Batanghari, 2023)
The purpose of this research is to analyze the effects of tax risk, audit quality, institutional ownership, managerial ownership, and business size among 2019-2021 Indonesia Stock Exchange-listed manufacturing firms in the products and consumption sector. The sampling technique was carried out using a purposive sampling technique, namely selecting samples based on certain criteria and systematics with the aim of obtaining a representative sample. Based on the criteria above, the number of companies that meet the criteria is 81 companies. This study uses multiple regression analysis techniques with SPSS tools. The results show that tax risk has a positive impact on the cost of capital, audit quality has a negative impact on the cost of capital, institutional ownership has a negative impact on the cost of capital, managerial ownership has a negative impact on the cost of capital, firm size has a positive impact on the cost of capital.